إجراءات دمج التجارة غير الرسمية في الإقتصاد الرسمي في الجزائر - عدوي، هاجر; عزيزي، نذير (جامعة الوادي University of Eloued, 2025)
تهدف الدراسة إلى فهم وَاقع التّجارة غيْر الرّسمية في الجَزائر مع تركيز خاص على الأنشطة المحورية في أَسواق التّجزئة والجملة. تتناول الدراسة تحديد الفئات الاجتماعية والاقتصادية المنخرطة فيه هذه التجارة، بالإضافة الى الإجراءات والسياسات التي إعتمدتها السّلطات العُمومية الْجزائرية ودورها في تشجيع التّجار غيرَ الرّسميين على الإنتقال الى القِطاع الرّسمي . من خلال إستخدام المنهج الوصفي التحليلي وأدوات الدراسة المتمثلة في الاحصائيات والتقارير توصلت الدراسة الى انه على الرغم من الجهود المبذولة من طرف الحكومة لا تزال التِجارة غير اْلرسمية موجودة بشكل كبير في السوق الجزائرية، مما يستدعي ضرورة استمرار تقييم السياسات الحُكومية وتكييفها بما يتناسب مع إحتياجات الْتجار غِير الْرسميين لتحقيق دَمج فعال ومستدام في الْاقتصاد الْرسمي. The aim of this study is to understand the reality of informal trade in Algeria, with a particular focus on the key activities in retail and wholesale markets. The study adresses the identification of the social and economic groups involved in this trade, as well as the measures and policies adopted by the Algerian public authorities and their role in encouraging informal traders to transition to the formal. Through the use of the descriptive analytical method and its study tools including statistics and reports, the study concludes that despite the efforts made by the govermment, informal trade remains significantly présent in the Algerian market. This necessitates the ongoing évaluation of govermment policies and their adaptation to meet the needs of informal traders to achieve their effective and sustainable integration into the formal economy.
Measures for integrating informal trade into the formal economy in Algeria: A study of informal retail and wholesale markets
مقال
Keywords: تِّجارة غير رسمية; أسواقْ تَّجزئة وجملة غيرِ الْرّسمية; قِطاع رَّسمي; formal sector; informal retail and wholesale markets